1994
DOI: 10.1103/physrevd.49.2729
|View full text |Cite
|
Sign up to set email alerts
|

Gravity and the domain-wall problem

Abstract: It is well known that the spontaneous breaking of discrete symmetries may lead to conflict with big-bang cosmology. This is due to formation of domain walls which give unacceptable contribution to the energy density of the universe. On the other hand it is expected that gravity breaks global symmetries explicitly. In this work we propose that this could provide a natural solution to the domain-wall problem.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
88
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(88 citation statements)
references
References 28 publications
0
88
0
Order By: Relevance
“…In this case, it can be shown that the vacuum degeneracy connecting the two sides of the CP domain wall is lifted, resulting in a wall annihilation driven by the decay of a false vacuum. More interestingly, assuming that gravity breaks global discrete symmetries explicitly, then there is probably no domain-wall problem at all (Dvali and Senjanovic, 1995;Rai and Senjanovic, 1994). These few examples show that although this problem arises whenever CP is spontaneously broken, it is possible to overcome it independently of the dynamics behind the symmetry breaking.…”
Section: F On the Origin Of Cp Violationmentioning
confidence: 99%
“…In this case, it can be shown that the vacuum degeneracy connecting the two sides of the CP domain wall is lifted, resulting in a wall annihilation driven by the decay of a false vacuum. More interestingly, assuming that gravity breaks global discrete symmetries explicitly, then there is probably no domain-wall problem at all (Dvali and Senjanovic, 1995;Rai and Senjanovic, 1994). These few examples show that although this problem arises whenever CP is spontaneously broken, it is possible to overcome it independently of the dynamics behind the symmetry breaking.…”
Section: F On the Origin Of Cp Violationmentioning
confidence: 99%
“…This cosmological catastrophe can of course be avoided by allowing explicit Z 3 breaking by terms suppressed by powers of the Planck mass which will ultimately dominate the wall evolution [851,852,853,854] without affecting the phenomenology of the model. One can also construct variations of the NMSSM which solve this domain wall problem.…”
Section: The Nmssmmentioning
confidence: 99%
“…It has been observed in [58] that parity breaking effects suppressed by Planck scale are sufficient to remove the DW. Black Holes can carry only locally conserved charges, and therefore there would exist processes in Quantum Gravity which do not conserve global charges as well as violate discrete symmetry such as parity.…”
Section: Cosmology Of Breaking and Soft Termsmentioning
confidence: 99%